2003
DOI: 10.1007/s00428-003-0877-0
|View full text |Cite
|
Sign up to set email alerts
|

The promoter methylation status of the DNA repair gene O 6 -methylguanine-DNA methyltransferase in ulcerative colitis

Abstract: Patients with long-standing and extensive ulcerative colitis (UC) have an increased incidence of colorectal cancer (CRC). It has been reported that a DNA repair gene, O6-methylguanine-DNA methyltransferase (MGMT) is inactivated by promoter hypermethylation in sporadic CRCs. Hence, we investigated the promoter methylation status of MGMT by methylation specific polymerase chain reaction (PCR) in a total of 67 tissue samples (61 non-cancerous tissues and 6 cancer tissues) from 24 patients with UC. Promoter hyperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…Moreover, methylation of MGMT, hMLH1 and p16, have been demonstrated in chronically inflamed mucosa in IBD patients without dysplasia. 11,12,22 Thus, it is possible that the ''field defect'' that exists in HSPS may also occur in a subset of patients with IBD. Finally, serrated polyps in patients with HSPS typically reveal a high incidence of BRAF (43%), and a low incidence (7%) of KRAS, mutations.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, methylation of MGMT, hMLH1 and p16, have been demonstrated in chronically inflamed mucosa in IBD patients without dysplasia. 11,12,22 Thus, it is possible that the ''field defect'' that exists in HSPS may also occur in a subset of patients with IBD. Finally, serrated polyps in patients with HSPS typically reveal a high incidence of BRAF (43%), and a low incidence (7%) of KRAS, mutations.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, genome-wide mRNA and microRNA expression profiles differ substantially in IBD-associated and sporadic CRC 38–45 . Moreover, the broad patterns of gene hypermethylation have been shown to be similar 46–51 or different 37, 52–54 between IBD-associated and sporadic colorectal tumors. These molecular pathologic differences and similarities imply that pathways underlying malignant progression in the two conditions share certain commonalities, but are also largely unique.…”
Section: Introductionmentioning
confidence: 99%
“…The difference of clinicopathological feature of colorectal cancer associated with UC from sporadic cancer often comes up for discussion. Matsumura et al reported that methylation of a DNA repair gene O 6 -methylguanine-DNA methyltransferase (MGMT) is rare in UC-associated colorectal cancer, but in sporadic cancer, in contrast, it is rather common (Matsumura et al, 2003). On the other hand, Osborn et al reported that the eyes absent 4 gene (EYE4) is hypermethylated both in sporadic and in UC-associated colorectal cancer (Osborn et al, 2006).…”
Section: Resultsmentioning
confidence: 92%